2021
DOI: 10.1038/s41541-020-00270-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of mucosal Th17 memory responses by acellular pertussis vaccines enhances nasal Bordetella pertussis carriage

Abstract: Pertussis has made a spectacular rebound in countries that have switched from whole-cell (wPV) to acellular pertussis vaccines (aPV). Here, we show that, unlike wPV, aPV, while protective against lung colonization by Bordetella pertussis (Bp), did not protect BALB/c mice from nasal colonization, but instead substantially prolonged nasal carriage. aPV prevented the natural induction of nasal interleukin-17 (IL-17)-producing and interferon-γ (IFN-γ)-producing CD103+ CD44+ CD69+ CD4+-resident memory T (TRM) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 47 publications
2
34
2
Order By: Relevance
“…(43)(44)(45) Bordetella Pertussis CD69+CD4+T RM cells T RM cells produced IL-17 and IFN-g, thereby recruiting neutrophils and preventing their colonization in the nose. (46)(47)(48)(49) Influenza Viruses…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%
“…(43)(44)(45) Bordetella Pertussis CD69+CD4+T RM cells T RM cells produced IL-17 and IFN-g, thereby recruiting neutrophils and preventing their colonization in the nose. (46)(47)(48)(49) Influenza Viruses…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%
“…Most importantly, however, while protective against pertussis disease, pertussis vaccination has at best limited effects on the prevention of colonization by and transmission of B. pertussis [26]. Furthermore, experimental studies in baboons and mice suggest that acellular pertussis vaccination may result in prolonged nasal carriage of B. pertussis [26][27][28][29].…”
Section: Effect Of Pertussis Vaccination and The Recent Resurgence Ofmentioning
confidence: 99%
“…The recently developed baboon model recapitulates the nearly full spectrum of human pertussis, including paroxysmal cough [39] and airborne transmission of B. pertussis from animal to animal [49]. aP vaccination of baboons protected these animals from pertussis disease, but did not prevent infection and transmission [26], and in fact, similar to mice [27][28][29], prolonged nasal carriage of B. pertussis. In contrast, wP vaccination did not prolong nasal carriage in baboons, which cleared the infection faster than non-vaccinated baboons, although much less efficiently than convalescent baboons [26].…”
Section: The Importance Of Animal Modelsmentioning
confidence: 99%
“…While aPV have shown their protective efficacy against pertussis disease, several studies have suggested that they do not prevent B. pertussis infection and transmission [ 71 , 72 ]. In fact, murine studies suggest that aPV immunization may even prolong nasal carriage by inhibiting the recruitment of IL-17-producing resident memory T cells and neutrophils to the nasal tissue [ 73 ]. In contrast, live attenuated pertussis vaccines in which PT has been genetically inactivated have been shown in non-human primates to protect against both pertussis disease and nasal colonization [ 74 , 75 ].…”
Section: From Pt/pa To Apvmentioning
confidence: 99%